The nexus between tax revenue and government expenditure in Nigeria; evidence from Toda -Yamamoto causality test - Pantamee, Abdurrahman Adamu; Yola, Abdulnasir Turawa; Mas’ud, Abdulsalam (IJICC, 2020)
This paper investigates the causal relationship between three types of tax revenue and government expenditure in Nigeria. Infrastructural decay and the government’s inability to meet its responsibilities has raised concern about the relationship between tax revenues and government expenditure in Nigeria. The study employed the TodaYamamoto causality test for its ability to clearly show the causal relationship between variables. Empirical evidence shows a unidirectional causality from the three types of tax revenue and government expenditure in Nigeria. The study concludes that government expenditure is not yielding the desired objective of increasing tax broad. Therefore, the paper recommends that long term government expenditure and economic policies that will increase tax revenues are given more emphasis.